Prognosis after aortic valve replacement in dialysis patients: results from the Swedish Renal Registry. (3rd October 2022) - Vavilis, G; Back, M; Barany, P; Ruck, A; Szummer, K
Abstract: Background: The choice of aortic valve prosthesis in aortic stenosis patients is based on patient preference, preoperative age, life expectancy, need for anticoagulant therapy and valve durability. Major uncertainties remain regarding optimal prosthetic valve choice in dialysis patients. Objectives: The aim of the study was to compare the clinical outcomes after aortic valve replacement with mechanical (MAV) or bioprosthetic valves (BAV) in dialysis patients. Methods: We used the observational, prospective, multicenter cohort from the Swedish Renal Registry, which includes all dialysis patients in Sweden. The study included 294 dialysis patients with aortic stenosis who underwent aortic valve replacement with MAV or BAV (obtained from surgical procedure codes) between 2005 and 2018, either before (n=155) or after dialysis start (n=139). Comorbidities and net adverse clinical events (bleeding events, stroke and reoperation) were obtained from national registries and defined by International Classification of Diseases codes (ICD-10). The incidence rate (IR) of primary endpoint comprised of all-cause death, bleeding events, stroke and aortic valve reoperation, as well as only all-cause death rates between recipients of MAV or BAV were estimated with Kaplan – Meier curves. Results: The median age was 72 years (interquartile range [IQR]: 63.9, 77.3), 77% were males and 60% received mechanical valves. During a median follow-up of 1.49 years (IQR: 0.66–2.83), the primary endpoint occurred in 202 patients. Compared to BAV-recipients, those who received MAV had comparable IR of the primary end-point (40.1/100 person-years; [95% Confidence Interval (CI): 33.7–47.7], vs 36.2/100 person-years; [95% CI: 28.9–45.4], P=0.322) (Figure 1). Mortality rate at 1-year of follow-up was 28.9% without difference between recipients of MAV or BAV (68.8% in MAV-group and 57.6% with BAV; mortality rate MAV 33.3/100 person-year; (95% CI: 27.9–39.8) vs BAV 27.3/100 person-year; (95% CI: 21.5–34.6), P=0. 183)), (Figure 2). Additional statistical analysis of the secondary endpoint based on the occurrence of aortic valve intervention before or after dialysis start, was consistent with the main results. Conclusion: There is no difference in mortality and complication rates in dialysis patients who underwent aortic valve replacement with MAV or BAV. Funding Acknowledgement: Type of funding sources: None.